A Rare Case of Anomic Aphasia and Gerstmann Syndrome Induced by Hemorrhagic Stroke - Daniel Mahendrakrisna; Bagus Ngurah Mahasena Putera Awatara; Gede Suputra; Ni Wayan Nurlina Ekasari; Dian Kusumastuti Anggraeni Putri; Anak Agung Ayu Putri Laksmidewi (Magna Neurologica, 2025)
Background: Aphasia is a language disorder caused by brain damage, such as a stroke. Anomic aphasia, a rare subtype, impairs the ability to name objects or people while preserving fluency and comprehension. It is often associated with Gerstmann syndrome, which is characterized by acalculia, finger agnosia, left-right disorientation, and semantic aphasia. This report presents a case of a 61-year-old male with anomic aphasia and Gerstmann syndrome following a hemorrhagic stroke. Case: A 61-year-old male patient presented with sudden difficulty recalling the names of family members and objects. Imaging revealed an intracerebral hemorrhage in the left parietotemporooccipital lobe. The patient also exhibited left-right disorientation and finger agnosia, indicative of Gerstmann syndrome. The Aphasia Test for Rehabilitation Information Diagnosis (TADIR) confirmed the diagnosis of anomic aphasia. Although conservative treatment led to partial improvement, naming difficulties and associated deficits persisted. Discussion: Anomic aphasia primarily involves difficulties with naming, typically resulting from lesions in the dominant hemisphere, particularly the temporal and parietal lobes. Its coexistence with Gerstmann syndrome underscores the complexity of overlapping neurological deficits. The TADIR test was crucial in diagnosing and managing the patient's condition. Conclusion: This case highlights the importance of a thorough evaluation in aphasia cases, especially when rare syndromes like Gerstmann syndrome are involved. Early and accurate diagnosis enables targeted interventions that can improve patient outcomes.